Influence of the Capping Ligand on the Band Gap and Electronic Levels of PbS Nanoparticles through Surface Atomistic Arrangement Determination - García Gutiérrez, Diana Fabiola; Hernández Casillas, Laura Patricia; Cappellari, Maria Victoria; Fungo, Fernando; Martínez Guerra, Edgar; García Gutiérrez, Domingo Ixcóatl (2018)
ABSTRACT: Lead sulﬁde (PbS) nanoparticles were synthesized by chemical methods with diﬀerent sizes and diﬀerent capping ligands (oleic acid, myristic acid, and hexanoic acid), avoiding ligand exchange procedures, to study the eﬀect of characteristics of the capping ligands on their energy levels and band gap values. Experimental results (UV−vis−NIR, Fourier transform infrared, and Raman spectroscopies, cyclic voltammetry, transmission electron microscopy, and electron energy loss spectroscopy) showed a marked inﬂuence of the capping ligand nature on the electro-optical properties of PbS nanoparticles with a very similar size. Diﬀerences were observed in the atomistic arrangement on the nanoparticle surface and phonon vibrations with the diﬀerent capping ligands. These observations suggest that the electrooptical properties of PbS nanoparticles are not only determined by their size, through quantum conﬁnement eﬀects, but also strongly aﬀected by the atomistic arrangement on the nanoparticle surface, which is determined by the capping ligand nature.